Uploading Private Chat Screenshots on Social Media: How the Law Respond it? - Arsawati, Ni Nyoman Juwita; Bunga, Dewi; Antari, Putu Eva Ditayani; Chandra Satriana, Made Wahyu (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 12 No 2 (2023), 2023)
Personal chat is a personal communication conducted in two directions and concerns privacy in communication. The latest behavior of social media users shows considerable virtual openness. The social media users upload screenshots of their personal chat to their social media accounts and even send them to gossip accounts in social media. In this study, there are three issues discussed namely privacy rights in personal chats uploaded on social media, potential crime of uploading personal chats, and state legal responses to the spread of personal chat screenshot on social media. The right to privacy is basically giving the freedom to publish or not publish personal chat on social media. There are at least two privacies protected in personal chat namely the sender and recipient of the message, but they are not limited to people or things discussed in the personal chat. Uploading personal chat screenshots on social media has the potential to cause doxing (theft of personal data) and cyberbullying. Countries respond to these conditions with legal provisions in their respective countries. The act of spreading personal chat screenshot on social media has a legal consequence of a lawsuit for compensation for violations of personal data, criminal sanctions for defamation and cyberbullying.